Media and youth : a developmental perspective - Kirsh, Steven J.; Wiley InterScience (Online service) (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2010)
Media & Youth: A Developmental Perspective provides a comprehensive review and critique of the research and theoretical literature related to media effects on infants, children, and adolescents, with a unique emphasis on development.: The only textbook to evaluate the role of development in media effects research, filling a gap in the subject of children and media; Multiple forms of media, including internet use, are discussed for a comprehensive view of the subject; Developmental points of interest are highlighted at the end of each section to reinforce the importance of development in media.
Media in the lives of youth -- Media effect theories -- Media and academic effects -- The medical and social benefits of media use -- Advertising, consumer behavior, and youth -- Media and stereotyping -- Media influences on obesity, body image, and eating disorders -- The role of media in alcohol, tobacco, and drug use -- Media and the sexualization and sexual socialization of youth -- Violent media part 1 : comic books, music, and video games -- Violent media part 2 : traditional screen media -- Media effects : magnitude, risk, and media literacy.
Includes bibliographical references (pages 253-295) and index.
Print version record.
Keywords: Mass media and children; Mass media and teenagers; Technology and children; Adolescent Behavior; Mass media; Adolescent Development; Psychology, Adolescent; Massamedia; Kinderen; Ontwikkeling (psychologie); Kind; Jugend; Massenmedien; Electronic books